2023
DOI: 10.1021/acs.cgd.3c00515
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrate Faceting on Epitaxial Lead Sulfide Thin Films Deposited from a Solution onto GaAs(100)

Taissia Rudnikov-Keinan,
Vladimir Ezersky,
Nitzan Maman
et al.

Abstract: Lead sulfide (PbS) thin films were deposited from a solution onto chemically etched GaAs substrates. The substrates were etched using two different chemical etchants, citric acid and phosphorous acid, resulting in different substrate roughness values from 0.4 nm up to 6.2 nm. In both cases, etching resulted in the simultaneous exposure of (100), (111), and (311) microfacets. These different substrate conditions had a strong impact on the morphology and microstructure of the PbS films. This work provides the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The primary distinction between PbS films deposited from solution on patterned GaAs(100) and GaAs(111)­A substrates is shown in Figure In the case of GaAs(100) the PbS film exhibits interruptions and distinct characteristics in the trench/line regions from those observed on the trench slopes (Figure a). Deposition within the trench/line regions occurs on smooth GaAs(100) facets, resulting in [001] PbS ∥[11̅0] GaAs zone axes and (1̅1̅0) PbS ∥(100) GaAs orientation relations (Figure b), in agreement with previous studies; heterotwinning is observed with a {111} twin plane and ⟨112⟩ twinning direction . In contrast, growth on the slopes takes place on GaAs(111) facets, giving rise to [11̅0] PbS ∥[11̅0] GaAs zone axes and (111) PbS ∥(111) GaAs orientation relations (refer to Figure c,e), creating heterotwinning relation {111}/⟨112⟩.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The primary distinction between PbS films deposited from solution on patterned GaAs(100) and GaAs(111)­A substrates is shown in Figure In the case of GaAs(100) the PbS film exhibits interruptions and distinct characteristics in the trench/line regions from those observed on the trench slopes (Figure a). Deposition within the trench/line regions occurs on smooth GaAs(100) facets, resulting in [001] PbS ∥[11̅0] GaAs zone axes and (1̅1̅0) PbS ∥(100) GaAs orientation relations (Figure b), in agreement with previous studies; heterotwinning is observed with a {111} twin plane and ⟨112⟩ twinning direction . In contrast, growth on the slopes takes place on GaAs(111) facets, giving rise to [11̅0] PbS ∥[11̅0] GaAs zone axes and (111) PbS ∥(111) GaAs orientation relations (refer to Figure c,e), creating heterotwinning relation {111}/⟨112⟩.…”
Section: Resultssupporting
confidence: 89%
“…On the one hand, substrate roughness allows for an increased density of preferred nucleation sites per unit area. Furthermore, previous research has shown that alteration of the crystallographic characteristics of the GaAs surface due to chemical etching, which results in exposure of (111) facets, is accompanied by an increase in growth rate . These considerations lead to the conclusion that increased trench width (smaller density of prismatic facets) should have resulted in slower growth rate, yet our results show the opposite behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations